QARAQALPAQ BAQSÍ – JÍRAWLARÍNÍŃ TARIYXÍY DÓRETIWShILIK ÓNERLERI MENEN TANÍSTÍRÍW USÍLLARÍ - Axetova, G.J. (SCIENCE and SOCIETY, 2023)
This article talks about using interactive methods in music lessons. The concepts of storytellers and the epic are considered. The rules are noted for executing methods.